Delivering the Full Potential of Oxygen Evolving Electrocatalyst by Conditioning Electrolytes at Near‐Neutral pH. Issue 6 (4th February 2021) - Nishimoto, Takeshi; Shinagawa, Tatsuya; Naito, Takahiro; Takanabe, Kazuhiro
Abstract: This study reports on the impact of identity and compositions of buffer ions on oxygen evolution reaction (OER) performance at a wide range of pH levels using a model IrO x electrocatalyst. Rigorous microkinetic analysis employing kinetic isotope effects, Tafel analysis, and temperature dependence measurement was conducted to establish rate expression isolated from the diffusion contribution of buffer ions and solution resistance. It was found that the OER kinetics was facile with OH − oxidation compared to H2 O, the results of which were highlighted by mitigating over 200 mV overpotential in the presence of buffer to reach 10 mA cm −2 . This improvement was ascribed to the involvement of the kinetics of the local OH − supply by the buffering action. Further digesting the kinetic data at various buffer p K a and the solution bulk pH disclosed a trade‐off between the exchange current density and the Tafel slope, indicating that the optimal electrolyte condition can be chosen at a different range of current density. This study provides a quantitative guideline for electrolyte engineering to maximize the intrinsic OER performance that electrocatalyst possesses especially at near‐neutral pH. Abstract : A buffer for OER : Rigorous microkinetic analysis using the IrO x electrocatalyst reveals that OH − is most likely the reactant for the oxygen evolution reaction (OER) in near‐neutral buffered conditions whereby buffering species function to maintain the concentration of OH − . Digesting the OER kinetic data discloses a trade‐off relationship between the exchange current density and the Tafel slope value, determining the optimal electrolyte condition at a given current density.